A Molecular Approach for Detecting Stage-Specific Predation on Lygus hesperus (Hemiptera: Miridae). Issue 6 (21st December 2020) - Hagler, James R; Casey, Miles T; Hull, Allya M; Machtley, Scott A
Abstract: A molecular gut analysis technique is described to identify predators of Lygus hesperus (Knight), a significant pest of many crops. The technique is unique because it can pinpoint which life stage of the pest was consumed. Sentinel egg masses designed to mimic the endophytic egg-laying behavior of L. hesperus were marked with rabbit serum, while third instar and adult L. hesperus were marked with chicken and rat sera, respectively. Then, the variously labeled L. hesperus life stages were introduced into field cages that enclosed the native arthropod population inhabiting an individual cotton plant. After a 6-h exposure period, the predator assemblage, including the introduced and native L. hesperus population, in each cage were counted and had their gut contents examined for the presence of the variously marked L. hesperus life stages by a suite of serum-specific enzyme-linked immunosorbent assays (ELISA). The whole-plant sampling scheme revealed that Geocoris punticpes (Say) and Geocoris pallens Stal (Hemiptera: Geocoridae) and members of the spider complex were the numerically dominant predator taxa in the cotton field. The gut content analyses also showed that these two taxa appeared to be the most prolific predators of the L. hesperus nymph stage. Other key findings include that Collops vittatus (Say) (Coleoptera: Melyridae) and Solenopsis xyloni McCook (Hymenoptera: Formicidae) appear to be adept at finding and feeding on the cryptic L. hesperus egg stage, and that L. hesperus, albeit at low frequencies, engaged in cannibalism. The methods described here could be adapted for studying life stage-specific feeding preferences for a wide variety of arthropod taxa.